Asthma similarities across ProAR (Brazil) and U-BIOPRED (Europe) adult cohorts of contrasting locations, ethnicity and socioeconomic status. (January 2020) - Cruz, Alvaro A.; Riley, John H.; Bansal, Aruna T.; Ponte, Eduardo V.; Souza-Machado, Adelmir; Almeida, Paula C.A.; Biao-Lima, Valmar; Davis, Maggie; Bates, Stewart; Adcock, Ian M.; Sterk, Peter J.; Chung, Kian Fan; et al.
Abstract: Background: Asthma prevalence is 339 million globally. 'Severe asthma' (SA) comprises subjects with uncontrolled asthma despite proper management. Objectives: To compare asthma from diverse ethnicities and environments. Methods: A cross-sectional analysis of two adult cohorts, a Brazilian (ProAR) and a European (U-BIOPRED). U-BIOPRED comprised of 311 non-smoking with Severe Asthma (SAn), 110 smokers or ex-smokers with SA (SAs) and 88 mild to moderate asthmatics (MMA) while ProAR included 544 SA and 452 MMA. Although these projects were independent, there were similarities in objectives and methodology, with ProAR adopting operating procedures of U-BIOPRED. Results: Among SA subjects, age, weight, proportion of former smokers and FEV1 pre-bronchodilator were similar. The proportion of SA with a positive skin prick tests (SPT) to aeroallergens, the scores of sino-nasal symptoms and quality of life were comparable. In addition, blood eosinophil counts (EOS) and the % of subjects with EOS > 300 cells/μl were not different. The Europeans with SA however, were more severe with a greater proportion of continuous oral corticosteroids (OCS), worse symptoms and more frequent exacerbations. FEV1 /FVC pre- and post-bronchodilator were lower among the Europeans. The MMA cohorts were less comparable in control and treatment, but similar in the proportion of allergic rhinitis, gastroesophageal reflux disease and EOS >3%. Conclusions: ProAR and U-BIOPRED cohorts, with varying severity, ethnicity and environment have similarities, which provide the basis for global external validation of asthma phenotypes. This should stimulate collaboration between asthma consortia with the aim of understanding SA, which will lead to better management. Highlights: The populations compared are of diverse ethnicity and socioeconomic status. Europeans and Brazilians share multiple similarities, in spite of the differences. In severe asthma (SA), age, weight and proportion of former smokers are similar. FEV1% pre-BD and % of atopics are similar in those with SA across both continents. The proportion of those with blood eosinophil counts > 300/μl is comparable in SA.